The aid of computerized tomography in hemifacial spasm - (:unkn) unknown (My University, 1992)
Although the physiopathological mechanisms causing hemifacial spasm are not clearly understood, it is generally accepted that the causative factor is compression of the facial nerve at its root exit zone. In this paper we present seven cases of hemifacial spasm which were studied by dynamic CT scanning in the preoperative period, and treated with microvascular decompression. We suggest that CT scanning has considerable diagnostic value in disclosing the asymmetrical vascular formation causing root exit zone compression and that microvascular decompression should be the treatment of choice in this condition.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Tomography, X-Ray Computed; Male; Vertebral Artery; Facial Muscles; Cerebellopontine Angle; Dilatation, Pathologic; Facial Nerve Diseases; Nerve Compression Syndromes; Spasm; Vascular Diseases